PENGEMBANGAN MULTIMEDIA PEMBELAJARAN SD PADA MATERI CUACA TEMA 5 KELAS III - Fitriana Fitriana; Herni Herni; Yulita Dwi Lestari (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2020)
Multimedia plays an important role in making a process learning takes place effectively, interestingly, and efficiently. Therefore, As an effort to increase the effectiveness of learning, and overcome limited teaching aids and learning media such as multimedia, teachers are required to be creative to develop or create these media. Research purposes this is to create learning media that attract participants' learning interest students to learn the material "Weather theme 5 grade 3" correctly and with an attractive appearance so as to increase interest learning and understanding of learners. Media development in a multimedia used for modify the media development design adjusted according to the needs of the researcher. In the collector The data used in this research are data about the development process of media preparation and development with Weather material. Humans are data descriptive, namely reviews and input from material experts as well as media experts in accordance with data development procedures. Second, data that is suitable for use as multimedia media that is suitable for use as media is determined through the analysis of the validation results of media experts as well as material experts. The results of the validation by media experts as well as material experts show that the designed media is suitable for use as learning media in the form of multimedia.